De la pobreza a la recuperación de residuos. La recolección informal en Buenos Aires, Argentina (2002-2015) - Mariano D. Perelman; Verónica V. Puricelli (MediAzioni, 2024)
In Argentina, after the economic, social, and institutional 2001 crisis, there was a substantial rise in the number of people informally collecting and selling recyclable waste. This activity had been ongoing for a long time, but the significant increase brought attention to an activity previously regarded as unlawful and illicit. From then on, even with discontinuities and drifts, a clear trend was consolidated towards the incorporation of informal collectors (colloquially called cartoneros/as) in public solid waste management systems, which implies, among other factors, a significant improvement in their working conditions. This article examines the establishment of the waste collection circuit over time and how its various regulations have impacted the work processes of cartoneros. It also explores the political and social organizations developed by the collectors, enabling them to negotiate and dispute the terms of this implementation. From our analysis, we suggest that a progression from poverty to recovery occurred, despite poverty remaining a fundamental aspect of the activity.